Teorias de Spin-1: decomposição em helicidades, redução dimensional e imersão de calibre - Biazotti, Herbert Antonio [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
We have studied the physical content of the following models: Maxwell, Proca, Self-Dual and Maxwell-Chern-Simons. One method we have used is the decomposition in the so called helicity variables, which can be done in the Lagrangian formalism. It leads to the correct counting of degrees of freedom without choosing a gauge condition. The method separates the propagating modes from the non-propagating ones. The Hamiltonian of the MCS and the AD is calculated. The second method used here is the analysis of the sign of the imaginary part of the residues of the two-point amplitude of the theory, showing that the models analyzed are free of ghosts. We also carry the dimensional reduction of the Maxwell-Chern-Simons and Self-Dual models from D = 2+1 to D = 1 + 1 dimensions. Next, we show that the dimensional reduction of those equivalent models also leads to equivalent models in D=1+1. Even more interesting is the fact, demonstrated here, that those reduced models can also be connected via gauge embedding. So the gauge embedding of the Self-Dual model into the Maxwell-Chern-Simons theory is preserved by the dimensional reduction

Neste trabalho analisamos o conteúdo físico dos seguintes modelos: Maxwell, Proca, Auto-Dual e Maxwell-Chern-Simons. Um dos métodos usado é a Decomposição em Helicidades, na qual é possível fazer, a partir do formalismo lagrangiano, a contagem correta dos graus de liberdade sem necessidade de escolha de calibre, separando os modos propagantes dos n~ao propagantes. Em seguida a hamiltoniana do MCS e do AD _e calculada. O outro método usado é a análise de conteúdo físico através do sinal da parte imaginária dos resíduos da amplitude de dois pontos da teoria, mostrando que os modelos possuem conteúdo físico livre de fantasmas. Além desses métodos, é feita a redução dimensional do Maxwell-Chern-Simons e do Auto Dual de D=2+1 para D=1+1 dimensões. Em seguida mostramos que a redução dimensional desses modelos equivalentes leva a modelos reduzidos também equivalentes. Mais do que isto, mostramos que esses modelos reduzidos também podem ser relacionados via imersão de calibre. É como se a imersão de calibre do Auto-Dual no Maxwell-Chern-Simons fosse preservada pela redução dimensional
Keywords: Teoria de campos (Física); Simetria (Física); Calibração; Campos de calibre (Física); Imersão; Field theory (Physics)